The Develovment of Reading and Wruting Skills by Using Thai Final-Sound Letters Exercise for Prathom Suksa 2 Students, Ban Piang Luang School - Kongkaew, Siriluck; Pothasin, Varunee; Chanpan, Amnat (MCU Haripunchai Review, 2026)
This research aimed to 1) develop and evaluate the validity and appropriateness of a learning plan for reading and writing consonant-syllable words using skill exercises for Grade 2 students, and 2) compare the achievement in reading and writing consonant-syllable words before and after using the skill exercises for Grade 2 students. The research design was an experimental research. The sample consisted of 23 Grade 2/1 students at Ban Piang Luang School during the second semester of the 2022 academic year. The research instruments included: 1) six learning plans using consonant-syllable word exercises; 2) a reading and writing consonant-syllable word exercise and a 10-item pre- and post-test. Statistics used for data analysis included percentages, means, and standard deviations. The research results revealed that: 1) The effectiveness of the learning plan for developing reading and writing consonant-syllable words using skill exercises was determined. For Grade 2 students, the average effectiveness score for the lesson plan was 49.16, considered highly appropriate. 2) A pre-test of student achievement after using the lesson plan using skill practice exercises was conducted. For Grade 2 students, the average pre-test score was 10.73, or 35.77%, with the highest score being 18 and the lowest being 10. The average post-test score was 17.66, or 58.61%, with the highest score being 28 and the lowest being 19. The average learning progress score was 61.50, or 22.77%, with the highest score being 15 and the lowest being 4.